THE NATURE AND FUNCTIONS OF SPECIALIZED DICTIONARIES IN MODERN LEXICOGRAPHY - Xudoyqulova Marjona,; Mamarajabov Anvar,; Tog’aymurodova Parizod, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Specialized  dictionaries  play  a  crucial  role  in  modern  lexicography  by addressing  the  specific  linguistic  needs  of  particular  fields  such  as  medicine,  law, technology,  and  education.  Unlike  general-purpose  dictionaries,  they  focus  on terminology,  usage,  and  conceptual  clarity  within  a  defined  domain.  This  article explores  the  nature,  structure,  and  key  functions  of  specialized  dictionaries, highlighting their importance in academic, professional, and communicative contexts.